Single-excitation dual-color coherent lasing by tuning resonance energy transfer processes in porous structured nanowires. Issue 37 (9th September 2015) - Wang, Zhaona; Shi, Xiaoyu; Yu, Ruomeng; Wei, Sujun; Chang, Qing; Wang, Yanrong; Liu, Dahe; Wang, Zhong Lin
Abstract : Single-excitation dual-color coherent random lasing was achieved by tuning the resonance energy transfer process in porous structured nanowires. Abstract : Single-excitation dual-color coherent lasing was achieved in a mixed random system of a binary dye and the suspension of gold–silver porous nanowires with plenty of nanogaps. This greatly enhanced the local electromagnetic field in the visible range and guaranteed a low threshold and high Q factor (>10 000) operator for simultaneous dual-color lasing. By tuning the resonance energy transfer process in the stimulated emission, triple output modes (single chartreuse lasing, chartreuse and red dual-color lasing, and single red coherent lasing) were easily obtained. This triple-mode coherent random lasing introduces a new approach to designing multi-functional micro-optoelectronic devices for multi-color speckle-free imaging and interference.